2014
DOI: 10.1164/rccm.201406-1052oc
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Pulmonary Hypertensive Vascular Disease in Childhood. Data from the Spanish Registry

Abstract: In moderate to severe pediatric pulmonary hypertension, the prognosis is better in pulmonary arterial hypertension than in other Nice categories. In pediatric pulmonary hypertension age at diagnosis younger than 2 years is a risk factor for mortality, in addition to the previously established risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
50
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 41 publications
9
50
0
1
Order By: Relevance
“…Although the true incidence and prevalence of PH in the pediatric population remain uncertain, recent epidemiologic data from national or international registries estimated an annual incidence of 64 cases per million children. 1115 The incidence of idiopathic pulmonary arterial hypertension (IPAH) was 0.7 cases per million, which is slightly less than adult reports, and PAH associated with CHD was 2.2 cases per million. Past reports from pediatric registries have primarily emphasized that IPAH, heritable PAH (HPAH), and PAH associated with CHD constitute the majority of cases (WHO Group 1 disease).…”
Section: Insights Into Pediatric Pvd Gained From International Registmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the true incidence and prevalence of PH in the pediatric population remain uncertain, recent epidemiologic data from national or international registries estimated an annual incidence of 64 cases per million children. 1115 The incidence of idiopathic pulmonary arterial hypertension (IPAH) was 0.7 cases per million, which is slightly less than adult reports, and PAH associated with CHD was 2.2 cases per million. Past reports from pediatric registries have primarily emphasized that IPAH, heritable PAH (HPAH), and PAH associated with CHD constitute the majority of cases (WHO Group 1 disease).…”
Section: Insights Into Pediatric Pvd Gained From International Registmentioning
confidence: 98%
“…This study further showed that independent risk factors for mortality included etiology, age at diagnosis younger than 2 years, advanced functional class, and high right atrial pressure as assessed by right heart catheterization. 15 Although limited by its retrospective nature, this report provides a more accurate landscape that better reflects diverse causes of PH commonly seen in pediatric practice. However, as with data from the other registries, there is likely some selection bias of referral patients, as the number of newborns, infants, and children with BPD, DLD, and CF are likely under-represented.…”
Section: Insights Into Pediatric Pvd Gained From International Registmentioning
confidence: 99%
“…1 In our study, only around 33% of the CCB users had a record for right heart catheterization. The reported proportion of children with idiopathic PAH who received CCBs as monotherapy (and were acute responders) has been quite variable: 24% in a Dutch cohort, 23 11% in the French registry, 12 6% in the Spanish registry, 24 and 9% in the UK registry. 13 In the Reveal registry, 25 20% (43/211) of all PAH patients received CCBs as monotherapy (21/211) or in combination (22/211), and 42 of 43 patients had undergone acute vasoreactivity testing.…”
Section: Discussionmentioning
confidence: 99%
“…Although the true incidence and prevalence of PH in the pediatric population remain uncertain, recent epidemiologic data from national or international registries estimated an annual incidence of 64 cases per million children. (1721) The incidence of idiopathic PAH was 0.7 cases per million and PAH associated with CHD was 2.2 cases per million. Past reports from pediatric registries have primarily emphasized that idiopathic pulmonary arterial hypertension (IPAH), heritable PAH (HPAH), and PAH associated with congenital heart disease (CHD) constitute the majority of cases (e.g., WHO Group 1 disease).…”
Section: Definition and Classification Of Pediatric Phmentioning
confidence: 99%
“…More recently, del Cerro and coworkers published data from the Spanish PH Registry, which has provided more extensive information on disease incidence, prevalence and the impact of functional class, WHO Group and other factors on survival (21). The Spanish Registry included many forms of PH and thereby provides a more accurate picture of the nature of PH-related disorders in children than past studies.…”
Section: Definition and Classification Of Pediatric Phmentioning
confidence: 99%